315 The Agreement Analysis Between MALDI-TOF and Two Traditional Methods to Identify the Microorganisms. (11th January 2018) - Qian, Li; Camara, Tracy; Uddin, Salah; Gasson, Samuel
Abstract: Objectives: Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF) is a cost-effective, fast, and accurate new method for the identification of the microorganisms. The purpose of this study was to determine the agreement between MALDI-TOF and two traditional methods to identify the microorganisms. Methods: A total of 154 clinical specimens were collected by a hospital from January to April, 2016. All specimens, including 65 Gram-positive bacteria, 42 Gram-negative bacteria, 25 anaerobic organisms, and 22 yeasts, were simultaneously identified by Microflex LT MALDI-TOF (Bruker Diagnostics, Germany) and MicroScan Walkaway 96 Plus (Siemens, Germany) or RapID ANA II Panel (Thermo Scientific, UK). For MALDI-TOF, a small amount of the sample mixed with a matrix compound was placed in a chamber. Then the mass-to-charge was determined by its "time of flight." One traditional method was the MicroScan using rapid and conventional panels from fresh cultures for microbial identification. The other method was the RapID ANA II system, based on the microbial degradation of specific substrates detected by various indicator systems. Kappa values were used to assess the strength of agreements between MALDI-TOF and the two traditional methods on IBM SPSS Statistics version 24 (2016). Results: Overall, the MALDI-TOF and the two traditional methods were almost in perfect agreement at species level for all 154 samples (kappa 0.900, P < .05). Further analysis between MALDI-TOF and MicroScan on different groups of microorganisms showed that yeast had a kappa of 0.886 ( P < .05), Gram-negative bacteria had a kappa of 0.883 ( P < .05), and Gram-positive bacteria had a kappa of 0.839 ( P < .05). Even anaerobic bacteria showed a kappa value of 0.781 ( P < .05) between MALDI-TOF and RapID ANA II Panel. Conclusion: MALDI-TOF is a reliable system to replace MicroScan 96 and RapID ANA II for identifying the microorganisms.